Trading with the Informed and against the Uninformed: Flows and Positioning in the Global Currency Market - Aldo Barrios; Rob Franolic; Davide Giovanardi; Michael Melvin (Center for Economic Studies and ifo Institute (CESifo), 2022)
FX trade settlement data from CLS provides the most comprehensive view of the opaque market of OTC currency trades. We use the flows of investment funds and non-financial corporates and develop trading signals where the former reflects speculative strategies, while the latter trade for liquidity needs. The implication is we trade in the direction of the funds flows and trade against large corporate flows, which should be followed by price reversals. Trading with informed flows yields positive risk-adjusted performance. Incorporating the liquidity trades signal improves risk-adjusted performance and greatly lowers the tail risk of the model.
Keywords: F31; G15; 330; foreign exchange; currency flows; informed trading; currency investing